Miller, Frederick Douglass and the Fight for Freedom - McDonlad, Archie (Teaching History: A Journal of Methods, 1991)
Frederick Douglass, the extraordinary nineteenth-century black leader, is the subject of this lifeand-times treatment in this entry in the Makers of America Series. The series is edited by John Anthony Scott. A statement about the series on the book’s jacket claims that it is targeted for young adults and general readers, and a reading of the text confirms this claim. The reading level is appropriate for college undergraduates and advanced secondary students, and the book would work as an assigned reading for a class. The length is modest and the data and interpretations are not strenuous. The book opens with Douglass a witness to a beating of his aunt for refusing the sexual advances of her owner. Douglass was then seven years of age, his aunt only eight years older. From that slavery-damning opening, the narrative proceeds to enumerate the many evils and personal affronts associated with slavery in what might be termed a PG rating style if this were a movie. Maybe even a G rating. We read that Douglass was separated from his black mother at an extremely early age and did not know which local white was his father, although he had his suspicions; raised by grandparents and in the company of many cousins, at an appropriate working age he was turned over to his owner to begin his working life; he lived a sheltered life for a time as the companion of a contemporary white until sent to Baltimore while still a young man; he taught himself literacy skills with some assistance at first, but then when it was pointed out that this might make him rebellious, the assistance stopped; he learned the caulker’s trade in the shipyards, but experienced discrimination from fellow workers; and he ran away to the North with the assistance of a free black named Anna, whom he later married, and then became the show-case lecturer for the Garrisonian abolitionists.